2021
DOI: 10.1101/2021.05.28.446092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased screen of human transcriptome reveals an unexpected role of 3′UTRs in translation initiation

Abstract: Although most eukaryotic mRNAs require a 5ʹ-cap for translation initiation, some can also be translated through a poorly studied cap-independent pathway. Here we developed a circRNA-based system and unbiasedly identified more than 10,000 sequences in the human transcriptome that contain Cap-independent Translation Initiators (CiTIs). Surprisingly, most of the identified CiTIs are located in 3ʹUTRs, which mainly promote translation initiation in mRNAs bearing highly structured 5ʹUTR. Mechanistically, CiTI recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Our work has shown that the 5’UTR of HIF1α mRNA is necessary for the HIF-dependent hypoxic response by regulating HIF1α mRNA association with polysomes and regulatory proteins such as YB-1. In addition other work has shown the 3’ UTR of HIF1α also plays a positive role in regulating HIF1α mRNA translation rates by recruiting several translation initiations factors, including eiF3 and DHX29, which unwind the 5’UTR during translation initiation [22]. This work indicates that the 5’ and 3’ HIF1α UTRs act in concert to control HIF1α protein translation, indicating that examining the roles of UTRs in the context of an artificial reporter construct may miss the full picture of regulation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work has shown that the 5’UTR of HIF1α mRNA is necessary for the HIF-dependent hypoxic response by regulating HIF1α mRNA association with polysomes and regulatory proteins such as YB-1. In addition other work has shown the 3’ UTR of HIF1α also plays a positive role in regulating HIF1α mRNA translation rates by recruiting several translation initiations factors, including eiF3 and DHX29, which unwind the 5’UTR during translation initiation [22]. This work indicates that the 5’ and 3’ HIF1α UTRs act in concert to control HIF1α protein translation, indicating that examining the roles of UTRs in the context of an artificial reporter construct may miss the full picture of regulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using artificial reporter constructs have indicated that both the 5’ and 3’ UTRs of HIF1α can modulate translation rates through acting as internal ribosome entry sites (IRES), sites to recruit RNA binding proteins, or act as targets for miRNAs [13, 15]. However, the primary role for the endogenous HIF1α 5’UTR remains unclear, with conflicting studies using reporter constructs suggesting it represses translation through its complicated secondary structure [22], or activates translation by binding to specialised RNA-binding proteins to facilitate ribosome recruitment [15, 21]. As more recent work using genome editing approaches has indicated that reporter constructs investigating the role of UTRs do not always phenocopy the role of the endogenous UTRs in cells [23], we decided to modify the endogenous HIF1α 5’UTR in cells to investigate its function.…”
Section: Introductionmentioning
confidence: 99%